1997
DOI: 10.1177/000348949710600712
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Innervation of the Thyroarytenoid Muscle by a Branch from the External Division of the Superior Laryngeal Nerve

Abstract: The neuroanatomy of the larynx was explored in seven dogs to assess whether there is motor innervation to the thyroarytenoid (TA) muscle from the external division of the superior laryngeal nerve (ExSLN). In 3 animals, such innervation was identified. Electrical stimulation of microelectrodes applied to the ExSLN resulted in contraction of the TA muscle, indicating that this nerve is motor in function. This was confirmed by electromyographic recordings from the TA muscle. Videolaryngostroboscopy revealed impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 7 publications
1
49
1
1
Order By: Relevance
“…Those studies have shown that branches from the SLN seem to innervate both the thyroarytenoid (TA) and the posterior cricoarytenoid (PCA) muscles. 23,24,33,41 It is also known that injection of horseradish peroxidase into the internal branch of the SLN in resected human larynges results in anterogradely labeled axons not only in the CT, but also in the TA and PCA muscles, 42 bringing the classical neuroanatomical picture further into question. The reportedly small motor unit sizes of the laryngeal muscles 10,32 reflect the requirement for precise innervation.…”
mentioning
confidence: 99%
“…Those studies have shown that branches from the SLN seem to innervate both the thyroarytenoid (TA) and the posterior cricoarytenoid (PCA) muscles. 23,24,33,41 It is also known that injection of horseradish peroxidase into the internal branch of the SLN in resected human larynges results in anterogradely labeled axons not only in the CT, but also in the TA and PCA muscles, 42 bringing the classical neuroanatomical picture further into question. The reportedly small motor unit sizes of the laryngeal muscles 10,32 reflect the requirement for precise innervation.…”
mentioning
confidence: 99%
“…Interestingly, stimulation of the distal branch of the eSLN in this animal led to TA muscle contraction even after subsequent RLN transection, indicating a direct pattern of innervation from the PP through the eSLN directly to the TA muscle bypassing the RLN, as shown in Figure 4. This finding was not totally unexpected, since Nasri et al 11 showed the crossinnervation of the TA muscle by the eSLN in the canine model. The second group contained 2 experimental necks that showed a short latency response to TA muscle contraction that occurred during stimulation of the central branch of the PP.…”
Section: Discussionmentioning
confidence: 61%
“…By counterstaining neural tissue with Sihler's stain, Wu et al (15) dissected 27 human larynges and found a connection between the distal EBSLN and the recurrent laryngeal nerve (RLN) in 44% of cases, with either an intramuscular branch entering the thyroarytenoid muscle (TAM) or an anastomosis with the RLN just prior to its entrance into the TAM. Similarly, Nasri et al (16) reported in a canine model the presence of crossinnervation to the TAM in 3 of 7 dogs, with the bulk of the activity concentrated in the anterior third of the vocal cords. The microdissection study of 90 human larynges by Sañudo et al (17) found that a branch of the EBSLN continued to join the ventral branch of the RLN in 68% of the cadavers, as Maranillo et al (18) found a submucosal neural connection between the EBSLN and the RLN in the paraglottic space in 85% of 103 human larynges under ×4 to ×6 magnification.…”
Section: Anatomy Of the Ebslnmentioning
confidence: 69%